Permian-Jurassic Mahanadi and Pranhita-Godavari Rifts of Gondwana India:provenance from regional paleoslope and U-Pb/Hf analysis of detrital zircons - Veevers, J. J.; Saeed, Ayesha (Gondwana Research, 2009)
The Permian-Jurassic Mahanadi and Pranhita-Godavari Rifts are part of a drainage system that radiated from the Gamburtsev Subglacial Mountains in central Antarctica. From 12 samples we analysed detrital zircons for U-Pb ages, Hf-isotopes, and trace elements to determine the age, rock type and source of the host magma, and Tom model age. Clusters, in decreasing order of abundance, are (1) 820-1000 Ma, host magmas felsic granitoids with alkaline rock, (2) 1500-1700 Ma felsic granitoids, (3) 500 to 700 Ma mafic granitoids with alkaline rock, (4) 2400-2550 Ma granitoids, and (5) 1000-1200 Ma felsic and mafic granitoids, mafic rock, and alkaline rock. Tom ranges from 1.5 to 3.5 Ga. Joint paleoslope measurements and zircon ages indicate that the Eastern Ghats Mobile Belt (EGMB) and lateral belts and conjugate Antarctica are potential provenances. Zircons from the Gondwana Rifts differ from those in other Gondwanaland sandstones in their predominant 820-1000 Ma and 1500-1700 Ma ages (from the EGMB and conjugate Rayner-MacRobertson Belt) that dilute the 500-700 Ma (Pan-Gondwanaland) ages. The 1000-1200 Ma zircons reflect the assembly of Rodinia, the 500-700 Ma ones that of Gondwanaland; the other ages reflect collisions in the region. (C) 2009 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.